2002
DOI: 10.1046/j.1365-8711.2002.05004.x
|View full text |Cite
|
Sign up to set email alerts
|

U-, B- and r-band luminosity functions of galaxies in the Coma cluster

Abstract: A B S T R A C TWe present a deep multicolour CCD mosaic of the Coma cluster (Abell 1656), covering 5.2 deg 2 in the B and r bands, and 1.3 deg 2 in the U band. This large, homogeneous data set provides a valuable low-redshift comparison sample for studies of galaxies in distant clusters. In this paper we present our survey, and study the dependence of the galaxy luminosity function (LF) on passband and radial distance from the cluster centre. The U-, B-and r-band LFs of the complete sample cannot be represente… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
85
3
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 41 publications
14
85
3
1
Order By: Relevance
“…deg). A steepening of the faint end slope of the UV luminosity function in the outskirts of Virgo is expected since already observed in the optical bands in other clusters such as Coma (Beijersbergen et al 2002;Adami et al 2007Adami et al , 2008. The accurate morphological classification available for the VCC galaxies (from Binggeli et al 1985, those not catalogued in the VCC being classified as late-type dwarfs according to their optical morphology and blue colors) allows us to estimate the UV luminosity function separately for late-(Sa-Sm-Im-BCD) and early-type (E-S0a-dE-dS0) systems (see Fig.…”
Section: The Uv Luminosity Function Of the Central 12 Degmentioning
confidence: 52%
“…deg). A steepening of the faint end slope of the UV luminosity function in the outskirts of Virgo is expected since already observed in the optical bands in other clusters such as Coma (Beijersbergen et al 2002;Adami et al 2007Adami et al , 2008. The accurate morphological classification available for the VCC galaxies (from Binggeli et al 1985, those not catalogued in the VCC being classified as late-type dwarfs according to their optical morphology and blue colors) allows us to estimate the UV luminosity function separately for late-(Sa-Sm-Im-BCD) and early-type (E-S0a-dE-dS0) systems (see Fig.…”
Section: The Uv Luminosity Function Of the Central 12 Degmentioning
confidence: 52%
“…For example, this effect has been observed in several clusters such as Coma (Lobo et al 1997;Beijersbergen et al 2002;Adami et al 2007a) or Abell 496 (Boué et al 2008), and it was shown that the faint-end slope gives indications of the cluster formation history (see e.g. Adami et al 2007a, and references therein).…”
Section: Introductionmentioning
confidence: 88%
“…A certain portion can also be attributed to the inclusion of galaxies in cluster outskirts that are projected onto the central region. Beijersbergen et al (2002) published a study of the LF of the Coma Cluster in which they corrected the LF for projection effects by subtracting the contribution of the outer Coma LF that is projected onto the central region. The resulting ''deprojected'' LF was measured to be marginally flatter than the projected two-dimensional LF.…”
Section: A2 Deprojecting the Luminosity Functionmentioning
confidence: 99%
“…Since different morphological types are characterized by different LFs (Binggeli et al 1988), the cluster LF (integrated over all galaxy types) should not be universal. Indeed, some studies have provided evidence that the cluster LF does vary with clustercentric radius (e.g., Beijersbergen et al 2002;Hansen et al 2005;Popesso et al 2006). The main goal of this paper is to investigate the change in the cluster R C band LF as a function of clustercentric radius.…”
Section: Introductionmentioning
confidence: 99%